The Effect of Hypothyroidism on Surgical Outcomes Postabdominoplasty: A Case-control Study - Rawan ElAbd, MD; Becher Alhallabi, MD, FRCS (C); Salman AlSabah, MD, FRCS (C), FACS; Hisham Burezq, MD, FRCS (C), FAAP (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Hypothyroidism is common in surgical patients. The objective of this study is to determine the rate of short- and long-term complications after abdominoplasty for patients treated for hypothyroidism. Methods:. This is a retrospective chart review that enrolled consecutive patients undergoing abdominoplasty across a 5-year period. Cases had a preoperative diagnosis of overt hypothyroidism requiring thyroid replacement therapy, whereas controls are without thyroid disease. Groups were matched by age, gender, comorbidity status (hypertension and diabetes), smoking, and center of surgery in a 3:1 ratio. Results:. There was a total of 61 cases and 183 matched controls followed up for 18 months; most were women (n = 240, 98%) and between the ages of 31 and 45 years (n = 142, 58%). There were no significant differences between cases and controls in any of the sociodemographic and comorbidity status except for current BMI, which was higher for cases than the control (P < 0.05). The proportions of all other infections (4.5% versus 1.6%), wound dehiscence (4.7% versus 0.8%), dermatitis (4.7% versus 1.6%), and necrosis (2.3% versus 0%), hematoma (4.7% versus 2.5%) and seroma (2.3% versus 1.6%) formation were higher in cases but not significant (P > 0.05). LTCs were not statistically different across groups (P > 0.05). Conclusion:. This study did not find a significantly different higher risk of complications after abdominoplasty for patients treated for hypothyroidism.